Avaliação da tipologia de empreendedores utilizando o teste "Keirsey Temperament Sorter". O caso da Incubadora Tecnológica de Santa Maria - Mallman, Tagli Dorval Mairesse (2005)
This research has as objective the evaluation and development of a methodology for entrepreneurs selection and identification based in the Keirsey & Bates (1984) works. To achieve this objective the studies of Myers (1995), Kroeger & Thuesen (1988) besides Keirsey & Bates (1984) were central. By a qualitative exploratory study the research seeks for similarity among the Santa Maria incubator s entrepreneurs. It was applied to all the entrepreneurs and some workers the KEIRSEY TAMPERAMENT SORTER (Portuguese version). As a base for the study a bibliographic research of the following themes as been conducted: Entrepreneurship, Entrepreneurs characteristics, Organization Life Cycle, Factors of organizations failure, Personality theories (basically the type theories). Based in the study it was possible to correlate existing theories and the development of a methodology for the selection and the bettering of the incubator s entrepreneurs. At the end, two models are suggested: the first for the selection of new entrepreneur for the incubator, the second for the selection of the employee of the companies already created.